2007
DOI: 10.1002/jbm.a.31353
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of different FEA models for studying root fractures caused by wedge effect

Abstract: Finite element analysis (FEA) utilizing models with different levels of complexity are found in the literature to study the tendency to vertical root fracture caused by post intrusion ("wedge effect"). The objective of this investigation was to verify if some simplifications used in bi-dimensional FEA models are acceptable regarding the analysis of stresses caused by wedge effect. Three plane strain (PS) and two axisymmetric (Axi) models were studied. One PS model represented the apical third of the root entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…Numerous possible reasons for VRF have been reported in the literature including trauma (Pitts et al, 1983), excessive forces during root canal obturation (Yang et al, 1995;Mireku et al, 2010), wedging effects of spreaders during lateral condensation (Mireku et al, 2010;Pitts et al, 1983;Walton et al, 1984), loss of structural integrity of the tooth because of caries or access cavity preparation (Soares et al, 2007;Arola and Rouland, 2003) and decrease in dentine thickness because of intracanal preparation (Meira et al, 2008;Mireku et al, 2010;Cohen et al, 2006;Lertchirakarn et al, 2003a). Furthermore, the application of endodontic posts appears to bear additional risks resulting from excessive pressure during post cementation (Mireku et al, 2010;Yang et al, 1995), wedging effects of endodontic posts (Meira et al, 2008;Pitts et al, 1983;Walton et al, 1984) and volumetric expansion from corrosion of posts (Pitts et al, 1983;Walton et al, 1984;Yang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous possible reasons for VRF have been reported in the literature including trauma (Pitts et al, 1983), excessive forces during root canal obturation (Yang et al, 1995;Mireku et al, 2010), wedging effects of spreaders during lateral condensation (Mireku et al, 2010;Pitts et al, 1983;Walton et al, 1984), loss of structural integrity of the tooth because of caries or access cavity preparation (Soares et al, 2007;Arola and Rouland, 2003) and decrease in dentine thickness because of intracanal preparation (Meira et al, 2008;Mireku et al, 2010;Cohen et al, 2006;Lertchirakarn et al, 2003a). Furthermore, the application of endodontic posts appears to bear additional risks resulting from excessive pressure during post cementation (Mireku et al, 2010;Yang et al, 1995), wedging effects of endodontic posts (Meira et al, 2008;Pitts et al, 1983;Walton et al, 1984) and volumetric expansion from corrosion of posts (Pitts et al, 1983;Walton et al, 1984;Yang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained by Meira et al 10 have indicated that the axisymmetric model presents stress vectors with similar orientation but lower in magnitude than those detected by 2D analysis for elements in the vicinity of restoration post, and stress levels can therefore be overestimated by adopting 2D fi nite element analysis. It is worth mentioning that, despite eventual approximations due to the adoption of 2D rather than 3D analysis, the comparison between the models is considered to be valid, specifi cally in regard to the identifi cation of critical regions where cracks can nucleate and eventually propagate leading to the loss of structural integrity and fi nally ultimate fracture of the restored tooth.…”
Section: Introductionmentioning
confidence: 92%
“…However, some investigations have demonstrated that root post transmits masticatory loads to the tooth root and supporting structures [5][6][7][8][9] . Accordingly, research works related to the biomechanics of dental materials have been carried out to evaluate the effect of masticatory loads on the stress distribution within endodontically treated teeth restored with intra-radicular posts [10][11][12][13][14][15][16][17][18][19] . This allows one to pinpoint highly stressed regions where fracture is expected to initiate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations